26+72=

Simple and best practice solution for 26+72= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26+72= equation:


26+72=0

We simplify the equation to the form, which is simple to understand
26+72=0

We move all terms containing to the left and all other terms to the right.
0=0-26-72

We simplify left and right side of the equation.
0=-98

0=-98

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

 

See similar equations:

| 8x-2-5x-8=0 | | 4-2y=-2-6 | | -5-x=5-3x | | ab=ac | | 26+72=x | | 5x^3+20x^2-25x=0 | | 6-48= | | 36-30-5= | | 26+72=0 | | 4x^2-24=20x | | 6+48= | | -3(x-6)+4(x+1)=7x-10 | | x^2*x=128+x | | x^3-3x^2+54=0 | | -5u+6=42 | | x^2*x=8 | | 2x+0.8=5 | | 4x+10y=18 | | 2x/7+0.8=5 | | x/7-x=2x | | -12+-14= | | -8+3n=-8 | | 3n+18=n^2 | | [x+3]+8=10 | | y+x=0 | | -128=4-4(4m+5) | | y=-3x^2-12x-6 | | -4+x=2+3x | | 3x-8=7(x-8) | | t/6+1=3 | | 8(h-1)=6h+4+2b | | -t/6+1=3 | | 3x-(x+1)-1=-x+4(2-x) | | y^2-11y+8=16 | | -2+x=p+14+p | | 2m+m+m+10=180 | | (5b-3b^3+6b^5)-(5b^3-8b^5-4b)= | | 3x-13=-2x+17 | | t^2+25= | | 15d^2-4d=0 | | 7x-7y=7 | | -6v+5(v+3)=-3+6(v-4) | | .05x+.1(x+5)=2.30 | | x/8+12=-5 | | 3x+14=6-x | | 6x-4(x-5)-(5-3x)=0 | | 23-4x=2x+5 | | -r/2-12=-27 | | x-4x-52=26 | | 3xy-y=8 | | 5x-4=-3 | | 6x-3y=-33 | | 4x^2+20x-144= | | 3(5x-7)-14x=3 | | q^2+8=-9q | | y=x^2+3x+2.25 | | 8x+12=3x+32 | | 85=5+4x | | 11.7*2= | | n^2+25n+144=0 | | y^3+4y^2=21y | | 4x+55=10x-85 | | 2n^2+1=16n^2 | | .15x=40+0.5x | | -12x^2-4x+8=0 |